Large Vertex Epidural Hematoma: Case Report and Review of Surgical Approaches - Silva Neto, Angelo R.; Medeiros, Luana; Silva, Fábio B.; Velloso, Renata N. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Vertex epidural hematomas (VEHs) are a special clinical entity due to their clinical presentation, vascular etiology and options of surgical approach. The clinical suspicion involves recognizing the mechanism of the injury and the correct visualization of the hematoma in computed tomography (CT) coronal sequences. In the present article, we describe a case of a very large (146 mL) VEH with central brain herniation, and provide a technical note on the surgical planning and treatment. A 34-year-old male patient was admitted to the hospital after an injury on the left superior parietal region. The Glasgow coma scale score was 6, and the left pupil of the patient was dilated. The CT scan showed a large epidural hematoma on the vertex between the coronal e lambdoid sutures, and a fracture over the sagittal suture. During the surgery, multiple burr holes were made laterally to the sagittal suture, and after inspection and no visualization of bleeding in the superior sagittal sinus (SSS), we performed a standard biparietal craniotomy. The patient was discharged three days after the surgery without any deficits. Currently, with the improvement in imaging modalities, more cases of VEH are being identified. Identifying the etiology prior to the craniotomy is challenging in severe cases. Tears in the SSS can bleed profusely, and they demand strategies during the craniotomy. With multiple burr holes parallel to the sagittal suture, we can visualize whether there is bleeding in the SSS and design a craniotomy with or without a central osseous bridge to anchor the dura. Neurosurgeons must be prepared to plan a surgical strategy in cases of large VEHs. Due to its rare frequency and bleeding risks, VEHs are considered challenging.
Keywords: vertex epidural hematoma; traumatic brain injury; craniotomy